EVALUASI KINERJA KEUANGAN PERUSAHAAN KONSTRUKSI DI BURSA EFEK INDONESIA DENGAN PENDEKATAN DUPONT - Saleh, Rahmat; Dadang Iwan Riswandi; Iman Firmansyah; Asty Khairi Inayah Syahwani; Lesia Fatma Ginoga (Politeknik Ubaya, 2025)
This study aims to evaluate the financial performance of construction companies listed on the Indonesia Stock Exchange during the 2019–2023 period using the DuPont System approach. The analysis focuses on three sample companies, PT Total Bangun Persada Tbk, PT Acset Indonusa Tbk, and PT Adhi Karya (Persero) Tbk by measuring Net Profit Margin (NPM), Total Asset Turnover (TATO), and Return on Investment (ROI). The results indicate that PT Total Bangun Persada Tbk consistently recorded the strongest financial performance, with an average ROI of 4.29%. In contrast, PT Acset Indonusa Tbk experienced significant financial pressure, with an average negative ROI of (13.33)%, while PT Adhi Karya (Persero) Tbk showed fluctuating performance, averaging an ROI of 0.68%. The industry average remained negative, reflecting the ongoing challenges in profitability and asset efficiency faced by the construction sector. These findings highlight the importance of asset management optimization and operational efficiency strategies to enhance the competitiveness of construction companies in Indonesia.